Consumption Of Junk Food And Awareness Regarding Its Effects On Health Among Adolescents Of A Selected Public School In Birgunj (Journal of Pharmaceutical Negative Results, 2022)
Globalization and urbanization have greatly affected one's eating habits and forced to consume high calorie fast foods, popularlyknown as Junk foods. Coronary artery disease, obesity and diabetes mellitus has significant rise due to junk food consumption. Theobjective of the study was to find out consumption and awareness regarding health hazards of Junk food among adolescents. Thefindings of the study revealed that majority (89.1%) of the adolescents had high level of consumption of junk food. Most adolescents(76%) had low awareness level regarding health hazards of junk food consumption. There was no significant association between thelevels of awareness regarding health hazards of junk food consumption with selected socio-demographic characteristics ofadolescents. . Methodology- A Descriptive cross sectional study was conducted among 129 adolescents of Public School, Birgunjselected by using disproportionate stratified random sampling technique. Data were collected by using pre tested Self-administeredstructured questionnaires. Data analysis was done using Descriptive statistics such as frequency and percentage. Inferential statisticslike Chi square test was used to find out association between levels of awareness regarding health hazards of junk food consumptionwith selected Socio-demographic variables of adolescents. Result- The study concluded that there was high consumption level andlow awareness level regarding health hazards of junk food consumption among adolescents. So, this study could be important indesigning the community based interventions where teachers and school administration can organize awareness programs onconsumption and awareness regarding health hazards of junk food among adolescents and parents in adopting strategies.